Experimental studies of thin-walled steel roof battens subject to pull-through failures. (15th April 2016) - Sivapathasundaram, Mayooran; Mahendran, Mahen
Highlights: Conducted an extensive experimental study on the pull-through failures of roof battens under wind uplift loads. Both small and full scale tests of roof battens were undertaken. Identified the critical parameters that significantly affect batten pull-through loads. Demonstrated the inadequacy of existing design rules. Developed suitable design rules and capacity reduction factors. Abstract: Despite the increasing usage of thin and high strength steel roof battens in the roof structures of low-rise buildings, recent cyclones and storms have shown that they prematurely fail at their screw fastener connections to the rafters or trusses due to the screw heads pulling through the batten bottom flanges. Such pull-through failures can lead to catastrophic failures of the entire roofing systems as observed during recent high wind events. Therefore a detailed experimental study consisting of both small scale and full scale tests was undertaken to investigate the pull-through failures of roof battens under wind uplift loading in relation to many critical parameters such as screw fastener tightening, roof batten geometry, batten thickness, steel grade, screw fastener head size and screw fastener location. Effects of underside surface and edge details of the screw fastener head, and screw fastener types were also considered. This paper presents the details of the tests conducted in this study and the pull-through failure load results obtained from them. Finally it presents the details of suitable design rules and capacity reduction factors developed in this study that can be used to accurately determine the design pull-through capacities of steel roof battens under wind uplift loads.